Psychological intervention to alleviate distress in haematopoietic stem cell transplantation: a phase II study - Baliousis, Michail (2016)
Background. Haematopoietic stem cell transplantation (HSCT) is an intensive procedure associated with psychological distress particularly during the first weeks (acute phase). Based on the self-regulatory model of adjustment to illness, a preparatory group intervention was developed aiming at alleviating distress by reducing negative perceptions of HSCT and fostering helpful coping.